2019
DOI: 10.1039/c9qm00133f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures and elastic properties of a family of metal-free perovskites

Abstract: The fundamental electronic structures and elastic properties of a family of metal-free perovskites were systematically investigated using a combined theoretical-experimental approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…The absorption coefficient was unusually small, <30 cm −1 , at saturation absorption at short wavelengths. From the elemental assignment of the partial density of states (PDOS) for DABCONH 4 Br 3 ( Figure 6B), we noted that the valence band maximum (VBM) was predominantly Br p-states while the conduction band minimum (with an overall weak DOS, which might help to explain the low absorption coefficient) was predominantly C (from DABCO) and N (which could come from either/both DABCO or/and ammonium), as well as some H. The other studies that showed elemental PDOS breakdown in their DOS [16,28,29] can be interpreted to agree with this, except for ref. [28], where the A cation was piperazine, and the conduction band minimum (CBM) appeared to be composed of halide s orbitals.…”
Section: Optoelectronic and Charge-transport Propertiesmentioning
confidence: 87%
See 3 more Smart Citations
“…The absorption coefficient was unusually small, <30 cm −1 , at saturation absorption at short wavelengths. From the elemental assignment of the partial density of states (PDOS) for DABCONH 4 Br 3 ( Figure 6B), we noted that the valence band maximum (VBM) was predominantly Br p-states while the conduction band minimum (with an overall weak DOS, which might help to explain the low absorption coefficient) was predominantly C (from DABCO) and N (which could come from either/both DABCO or/and ammonium), as well as some H. The other studies that showed elemental PDOS breakdown in their DOS [16,28,29] can be interpreted to agree with this, except for ref. [28], where the A cation was piperazine, and the conduction band minimum (CBM) appeared to be composed of halide s orbitals.…”
Section: Optoelectronic and Charge-transport Propertiesmentioning
confidence: 87%
“…[18] Refs. [16,18,[27][28][29] all calculated band structures for a variety of ANH 4 X 3 compounds and for a variety of reasons (including to predict/understand ferroelectric, mechanical, and nonlinear optical (NLO) properties). Ref.…”
Section: Optoelectronic and Charge-transport Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] These materials are nontoxic, mechanically flexible, and lightweight compared to traditional metal-based halide perovskites. The functionality of these materials has recently been explored as metal-free ferroelectrics, [4,9] mechanical/elastic properties, [10][11][12] and their non-linear optical properties have been reported in a theoretical study. [13] Unfortunately, 17 years after the initial discovery of metal-free halide perovskites, there have been no reports about their charge transport characteristics and only one report (see Supporting Information of ref.…”
mentioning
confidence: 99%